Comparative Transcriptomics Unravels Prodigiosin's Potential Cancer-Specific Activity Between Human Small Airway Epithelial Cells and Lung Adenocarcinoma Cells - Davient, Bala; Ng, Jessica Pei Zhen; Xiao, Qiang; Li, Liang; Yang, Liang (Frontiers in Oncology, 2018)
Objective: Non-small cell lung cancer (NSCLC) is extremely lethal upon metastasis and requires safe and effective systemic therapies to improve the patient’s prognosis. Prodigiosin (PG) appears to selectively and effectively target cancer but not healthy cells. However, PG’s cancer-specific activity has remained elusive until recently. Methods: PG’s cancer-specific performance was compared to Docetaxel (DTX), Paclitaxel (PTX), and Doxorubicin (DOX) against human lung adenocarcinoma (A549) and human small airway epithelial cells (HSAEC). Combination of PG with DTX, PTX or DOX in a 1:1 ED50 ratio was also evaluated. MTT assay was used to determine the post-treatment cell viability. RNA-sequencing was used for comparative transcriptomics analysis between A549 and HSAEC treated with 1.0µM PG for 24 hours. Results: PG reduced A549 cell viability by four-folds greater than HSAEC. In comparison to DTX, PTX and DOX, PG was approximately 1.7 times more toxic towards A549, and 2.5 times more protective towards HSAEC. Combination of PG in 1:1 ED50 ratio with DTX, PTX or DOX failed to exhibit synergistic toxicity towards A549 or protection towards HSAEC. In A549, genes associated in DNA replication were downregulated, while genes directly or indirectly associated in lipid and cholesterol biogenesis were upregulated. In HSAEC, co-upregulation of oncogenic and tumour-suppressive genes was observed. Conclusion: An overactive lipid and cholesterol biogenesis could have caused A549’s autophagy while a balancing-act between genes of oncogenic and tumour-suppressive nature could have conferred HSAEC heightened survival. Overall, PG appears to be a smart chemotherapeutic agent that may be both safe and effective for NSCLC patients.